Analysis of the factors that drive the hedonic behavior of - Prasna, Cornellan Hayden Setya; Riani, Lilia Pasca (Proceeding Kilisuci International Conference on Economic & Business, 2025)
Research aim : To analyze the factors driving hedonic behavior among students and its impact on academic performance and psychosocial conditions.Design/Method/Approach : The study employs a Mix Method Sequential Explanatory approach, consisting of qualitative data collection followed by quantitative surveys and in-depth interviews.Research Finding :Ten main factors influencing hedonic behavior were identified, including social media influence, social pressure, and lack of financial literacy, based on literature and survey data from 100 students.Theoretical Contribution/Originality : This research provides new insights into student consumptive behavior in the digital era by examining the role of social media and digitalization.Practical/Policy Implication : The findings can inform educational institutions, parents, and students in developing financial education and lifestyle management policies.Research Limitation : The study is limited to students in Yogyakarta and may not be generalizable to other regions or populations.